Optimasi Pengadaan Buku Perpustakaan Menggunakan Metode Algoritme Genetika (Studi Kasus: Perpustakaan Universitas Brawijaya) - Witriana Sumarni; Agus Wahyu Widodo; Muh. Arif Rahman (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Every year at Library of Brawijaya University procures books to increase the attractiveness of readers or to provide the best service for readers. However, to carry out a maximum book procurement, an adequate budget is needed for the needs of all books needed by each department in Brawijaya University. Therefore, in this study a system was created which was able to optimize the number of books obtained with the budget set in the library of Brawijaya University by applying the genetic algorithm method. Genetic algorithms generate chromosomes with permutation genetic algorithms, each gene represents 1 book title per department. After chromosome generation is carried out, a crossover reproduction process and mutation reproduction will be carried out to produce new individuals. Then an individual evaluation and selection is based on the highest fitness value. After testing, the results of the parameters of the best population were obtained = 160, parameters of many generations = 2000, crossover rate 0.5 and mutation rate 0.5 which gave the opyimal results of the library book procurenment by the number of book purchased 1077 books.